Ultraviolet-C (UV-C) Effectiveness for Bacterial Decontamination in The Hospital Setting: A Systematic Review (Journal of Health Sciences, 2024)
Introduction: Bacteria are the most common agent reported to cause hospital-acquired infection (HAI) and nurses play a key role in achieving optimal decontamination. Ultraviolet-C (UV-C) is a promising candidate to reduce the bacteria infection burden. Therefore, this review aims to explore the UV-C application and its effectiveness in reducing bacteria contamination on various objects that can act as sources of HAI transmission.Methods: Searches were conducted on the PubMed, ScienceDirect, Scopus, and Cumulative Index to Nursing and Allied Health Literature databases. The inclusion criteria were randomized clinical trials, and non-randomized clinical intervention studies, written in English and published between January 2018 and March 2023. The search strategy used a population (P), intervention (I), comparator (C), and outcome (O) approach.Results: A total of 21 eligible studies were included in this review with four being related to decontaminating medical devices, two to personal equipment, nine to communication devices, and the remaining six to the environment. The exposure to UV-C radiation varies ranging from 24 s to 24 h (continuously) and it reduced the level of bacteria even up to 100%. Meanwhile, previously the objects were detected to be contaminated with pathogenic and resistant bacteria.Conclusion: UV-C exposure can be effectively used to decontaminate various objects in hospitals. However, special consideration should be given to semi-critical devices due to contact with mucosal tissue. Further studies are needed regarding the application of doses and duration of UV-C exposure to eliminate bacteria completely.